The inducing of caspase and Bcl-2 pathway with royal jelly decreases the muscle tissue damage exposed with fluoride in rats - Aslan, Abdullah; Can, Muhammed Ismail; Gok, Ozlem; Beyaz, Seda; Parlak, Gozde; Ozercan, Ibrahim Hanifi (Springer Heidelberg, 2022)
In this study, 42 Wistar albino male rats (n = 42, 8 weeks old) were used. Rats were divided into 6 groups and 7 rats included each group. Groups: (i) Control group: Standard diet; (ii) RJ (royal jelly) group: Standard diet + royal jelly; (iii) F50 group: Standard diet + 50 mg/kg fluoride; (iv): F100 group: Standard diet + 100 mg/kg fluoride; (v) F50+RJ group: Standard diet + 50 mg/kg fluoride + royal jelly; (vi): F100+RJ group: Standard diet + 100 mg/kg fluoride + royal jelly. After 8 weeks, the rats were decapitated, and their muscle tissues were removed. Expression levels of Caspase-3, Caspase-6, Bax, tumor necrosis factor-alpha (TNF-alpha), interleukin 1 alpha (IL1-alpha) and Bcl-2 proteins in muscle tissue were determined by western blotting method. Histopathological analyses were also performed on the muscle tissue. Malondialdehyde (MDA), glutathione (GSH) and catalase (CAT) analyses were determined by a spectrophotometer. According to the obtained results, Bcl-2, TNF-alpha and IL1-alpha protein expression was increased in damage groups compared to the control and royal jelly groups, while Caspase-3, Caspase-6 and Bax protein expression levels decreased in damage groups. MDA level increased in damage groups compared to the control and royal jelly groups, while CAT and GSH levels increased with royal jelly application in royal jelly-given group in comparison to the flouride-exposed group. According to histopathological analysis results, edema and inflammatory cell formations were found in the injury groups, a tendency to decrease in these injuries was observed in the treatment groups. Based on these results, we can say that royal jelly has protective effects on muscle tissue against fluoride damage.
Keywords: Bax; Bcl-2; Fluoride; IL1-alpha; Muscle damage; Royal jelly; TNF-alpha